BULLYING IN THE HUNDRED DRESSES ANALYSIS OF ILLUSTRATED NOVEL (PANOPTICON: Journal of English Studies, 2022)
The aim of this study is to analyze the things that can trigger bullying in an illustrated novel, especially children's literature. The object of this study is an illustrated novel entitled The Hundred dresses. This study uses a qualitative method that presents analysis in illustrations and writings. To guide this study, the perspective of Olweus (1993) is used which can support the bullying issue presented. The result of this study is to find differences in the characteristics of names that come from Poland and the quiet behavior of the main character that triggers bullying, in addition, low social class is marked by the condition of the house being small and remote, the main character actually claims about a hundred dresses.  It doesn't match her look through the faded blue dress she wears every day. The main character is also bullied for trying to make friends with a popular girl at school with an excessive approach so that the main character tries to overcome bullying by changing her appearance and attitude by being more friendly, proving about the hundred dresses she has by winning a drawing contest and transferring to another school more suited to her life.Keywords: illustrative elements, narrative elements, bullying, struggle.